2018
DOI: 10.1038/gim.2017.249
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive Noonan syndrome associated with biallelic LZTR1 variants

Abstract: PurposeTo characterize the molecular genetics of autosomal recessive Noonan syndrome.MethodsFamilies underwent phenotyping for features of Noonan syndrome in children and their parents. Two multiplex families underwent linkage analysis. Exome, genome, or multigene panel sequencing was used to identify mutations. The molecular consequences of observed splice variants were evaluated by reverse-transcription PCR.ResultsTwelve families with a total of 23 affected children with features of Noonan syndrome were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(214 citation statements)
references
References 23 publications
11
202
1
Order By: Relevance
“…Exome sequencing in search of disease‐causing variants revealed a pair of compound heterozygous LZTR1 variants (NM_006767.4:c.1605C > A [p.Tyr535Ter] [rs753347937] and NM_006767.4:c.2387T > C [p.Ile796Thr] [rs141672122]) that have never been associated with a disorder before but here co‐segregated with phenotype. According to the American College of Medical Genetics and Genomics consensus criteria (Richards et al, ), the former nonsense variant was evaluated as “pathogenic” and the latter as “likely pathogenic.” In line with the literature, our patients harbored a combination of one null and one putatively hypomorphic variant, further supporting the proposed loss‐of‐function mechanism of the disease (Johnston et al, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Exome sequencing in search of disease‐causing variants revealed a pair of compound heterozygous LZTR1 variants (NM_006767.4:c.1605C > A [p.Tyr535Ter] [rs753347937] and NM_006767.4:c.2387T > C [p.Ile796Thr] [rs141672122]) that have never been associated with a disorder before but here co‐segregated with phenotype. According to the American College of Medical Genetics and Genomics consensus criteria (Richards et al, ), the former nonsense variant was evaluated as “pathogenic” and the latter as “likely pathogenic.” In line with the literature, our patients harbored a combination of one null and one putatively hypomorphic variant, further supporting the proposed loss‐of‐function mechanism of the disease (Johnston et al, ).…”
Section: Resultssupporting
confidence: 90%
“…Eighty percent of the patients carry dominant mutations in either the PTPN11 , KRAS , SOS1 , SOS2 , RAF1 , NRAS , BRAF , or RIT1 , all of which are members of the RAS/MAPK signaling cascade (Aoki, Niihori, Inoue, & Matsubara, ). Recently, recessive variants in the LZTR1 ( leucine‐zipper‐like transcription regulator 1 ) gene (OMIM #600574) were identified from genetic analyses of NS patients who had tested negative for known RAS/MAPK gene mutations (Johnston et al, ; Nakaguma, Jorge, & Arnhold, ; Umeki et al, ). LZTR1 is now emerging as a novel causative gene of NS pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…CBL, NRAS, and LZTR1 pathogenic variants were also detected in this study. In particular, germline LZTR1 pathogenic variants have been shown to be associated with NS in recent studies, which can follow either recessive or dominant inheritance patterns . In our study, two novel compound heterogeneous variants in the LZTR1 gene were identified in one patient with a typical NS phenotype, while neither her mother nor her father were clinically affected.…”
Section: Discussionmentioning
confidence: 50%
“…Noonan syndrome [NS (MIM 163950)] is an autosomal dominant/recessive disorder characterized by short stature, craniofacial dysmorphism, cardiac abnormalities, short and/or webbed neck, and cryptorchidism in male patients. Pathogenic variants in the genes encoding proteins implicated in the RAS‐MAPK signaling pathway are responsible for Noonan syndrome, leading to pathway dysregulation . Fifteen genes have been reported to be involved in NS to date: PTPN11, SOS1, RAF1, BRAF, HRAS, KRAS, NRAS, SHOC2, MAP2K1, MAP2K2, CBL, RIT1, RASA2, A2ML1 , and LZTR1 …”
Section: Introductionmentioning
confidence: 99%
“…Additional extracardiac features include neurodevelopmental disabilities, cryptorchidism, delayed puberty, lymphedema, bleeding disorders, and a slightly increased predisposition to hematologic and solid cancers (Roberts, Allanson, Tartaglia, & Gelb, ). Transmission was established to be autosomal dominant, although an autosomal recessive form has recently been identified (Johnston et al, ). The phenotype is variable, but penetrance is believed to be complete.…”
Section: Noonan Syndrome and The Rasopathiesmentioning
confidence: 99%